CORPORATE ENVIRONMENTAL DISCLOSURE DAN REAL EARNING MANAGEMENT DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI MODERASI - Irfan Saputra, (2023)
This study was conducted to examine the effect of corporate environmental disclosure on real earning management with managerial ownership as a moderating variable and leverage, external audit quality, firm size and profitability as control variables. In this study, corporate environmental disclosure is measured using the Environmental Disclosure Index (EDI) and real earnings management using abnormal operating cash flows, abnormal production costs, and abnormal discretionary costs. This research is a quantitative research with a fixed effect model. This study uses secondary data in the form of annual reports and corporate sustainability reports. The population in this study are non-financial companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used purposive sampling with a total sample of 198 from 66 non-financial companies in 2019-2021. The hypothesis test in this study used panel data regression using the STATA 14 application with a significance level of 5%. The results of the data analysis show that (1) corporate environmental disclosure has no effect on real earning management, (2) managerial ownership does not strengthen the effect of corporate environmental disclosure with real earning management.